Environmental Planning and Management of the Kathmandu Valley - Subedi, Bhim Prasad (Himalayan Review, 2011)
Not available. Key words: Environmental Planning; Management; Kathmandu Valley The Himalayan Review Nepal Geographical Society Vol. XXXII 2001 Page: 55-58 Uploaded date: 7 June, 2011